Marginal Tax Rates: Evidence from Nontaxable Corporate Bonds: A Note - ANG, JAMES; PETERSON, DAVID; PETERSON, PAMELA (Journal of Finance, 1985)
ABSTRACT This study offers an alternative method of calculating marginal personal tax rates through the pairing of nontaxable (industrial development and pollution control) and taxable corporate bonds. This procedure is shown to produce matched bond pairs that are comparable. Two hundred pairs of bonds are examined from the second quarter of 1973 through the second quarter of 1983. Testing of the marginal tax rate relationships indicates that the marginal personal tax rate is less than the corporate statutory tax rate.